2016
DOI: 10.4315/0362-028x.jfp-16-160
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stability of Ochratoxin A in an Aqueous Buffered Model System

Abstract: Ochratoxin A (OTA) represents one of the most widespread mycotoxins in agricultural commodities in the world and is considered a possible human carcinogen with its potent nephrotoxicity. OTA is stable under most food processing conditions; however, higher-temperature treatment may reduce OTA content in foods. Since OTA can be found in processed products destined for both human and animal consumption, factors affecting its stability or reduction during thermal processes were investigated here. The reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Although it seems that OTA is very stable at high temperatures and resistant to hydrolysis, some studies reported its reduction during baking (Vidal, Marín, Morales, Ramos, & Sanchis, ; Vidal, Morales, Sanchis, Ramos, & Marín, ). Dahal, Lee, Gu, and Ryu () studied the reduction of OTA during various heating times (up to 60 min) at different temperatures (100, 125, 150, 175, and 200ºC) in the aqueous buffer solutions at different pH (pH 4, 7, and 10). Over 90% of OTA was reduced at 200ºC in pH 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it seems that OTA is very stable at high temperatures and resistant to hydrolysis, some studies reported its reduction during baking (Vidal, Marín, Morales, Ramos, & Sanchis, ; Vidal, Morales, Sanchis, Ramos, & Marín, ). Dahal, Lee, Gu, and Ryu () studied the reduction of OTA during various heating times (up to 60 min) at different temperatures (100, 125, 150, 175, and 200ºC) in the aqueous buffer solutions at different pH (pH 4, 7, and 10). Over 90% of OTA was reduced at 200ºC in pH 4.…”
Section: Introductionmentioning
confidence: 99%
“…Over 90% of OTA was reduced at 200ºC in pH 4. After processing under an alkaline condition (pH 10) at 100ºC for 60 min, about 50% of the OTA was lost (Dahal et al, ). Valle‐Algarra et al (34) reported that about 30% of OTA was reduced during dough fermentation with S. cerevisiae , depending on the OTA levels added to the wheat flour (Valle‐Algarra et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, heating with NaOH (0.1 N) resulted in the decomposition and detoxification of ochratoxin A [ 37 ]. A recent study conducted in buffer solutions of different pHs (pH 4, 7 and 10) found that the rate and the extent of OTA reduction were dependent on pH, processing time, and temperature: an OTA reduction greater than 90% was achieved at 200 °C for all treatments except pH 4; about 50% of the OTA was lost after treatment at pH 10 and 100 °C for 60 min, while a significant OTA reduction was not observed after 60 min under neutral and acidic conditions at 100 °C [ 38 ]. However, the reduction of OTA under alkaline conditions might be due to the reversible conversion of OTA to the open lactone of ochratoxin A (OP-OTA), which was found to be more toxic than OTA in rats and mice [ 13 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pH of bread dough is usually in the range of 4.5–6.0, while the pH of biscuit or cookie dough is 7.0–7.2. OTA should be stable at both pH ranges as demonstrated by [ 38 ]. Therefore, it is no surprise that the cookie baking process did not reduce OTA in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Physical methods for OTA decontamination are not very efficient due to OTA's intrinsic stability. Heating up to 250 • C [12,13], intermittent ultrasonic treatment in an aqueous medium supplemented with alkali [14], gamma irradiation [15] and ultrafiltration [16] have been used to reduce the levels of OTA in different food commodities. Other detoxifying protocols include the adsorption over minerals or modified clays [17] and also chemical methods such as the treatment with reducing and alkylating agents [18,19].…”
Section: Introductionmentioning
confidence: 99%